Steven Osika: capstone - Osika, Steven, artist (Colorado State University. Libraries, 2017)
The artist's statement: I've learned that everything that exists in this world has gone through some form of design. It is a fundamental base for everything that is created and is existential to the world that surrounds us. Our minds are adapted to the way in which we interpret our physical realm and influences the decisions that we later make. My work strives to take hold of this opportunity in order to communicate messages through multiple avenues. Ideas of quality, cleanliness, and organization shine through the pieces that I have created and exemplify an illustrative nature.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design